Optimalisasi Peran Mahasiswa KKN dalam Gerakan Literasi Masyarakat Desa Rawaurip Kabupaten Cirebon - Moh. Yudi Mahadianto; Riki Radiyansyah; Ranti Pradita; Sarifhatul Aini Yuliyus Putri; Vickry Febrian; Nia Melita; Salsabila Rizqy Fatihah; Putri Amalia; Auliya Safitri; Sarah Naflah Nurfadhilah; Galih Andrianto; Muhammad Rafli Subagja; Mukhamad Ravi Razabi Al Qaushar; Fernando Yoga Lesmana; Rohayati Rohayati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The low literacy culture in rural areas, such as Rawaurip Village, Cirebon, is a real challenge. This research aims to optimize the role of students participating in the Community Service Program (KKN) at Swadaya Gunung Jati University in improving community literacy. Using a participatory approach, this program was developed in collaboration with village officials, the Cahaya Nusantara Community Learning Center (TBM), and the local community. Key activities include child literacy mentoring, TBM strengthening, digital literacy outreach, and literacy appreciation. Data collected through observations, questionnaires, and interviews showed positive results. There was a significant increase in children’s reading interest, visits to the TBM, and community participation in literacy programs. This research concludes that optimizing the role of KKN students can make a real contribution to strengthening village community literacy.